Asking key questions of self-reflection. Issue 1 (2nd January 2022) - Brownhill, Simon
ABSTRACT: The call for individuals to engage in reflection is increasingly prevalent across much of the world. To aid this, a wealth of practical paper-based manuals, online tutorials and face-to-face training is available to foster participant engagement. However, a noticeable gap in this support is evident when learners and professionals in the workforce are asked to 'self-reflect'. This thoughtpiece seeks to positively address this by offering a literature-based exploration of this critical skill; this is facilitated by asking and answering key questions such as what is self-reflection, why is it important, and how can it be practically undertaken. Efforts to encourage individuals to engage in creative self-reflective activity are fuelled by an explanation of the Self-Reflective Shapes approach that has been developed by the author. Written to be accessible in both content and scope, the discussion offered serves as an introductory 'go-to' that has the potential to help individuals self-reflect as part of their learning and/or professional development with improved clarity, appreciation and confidence.